Transgender abortion patients and the provision of transgender-specific care at non-hospital facilities that provide abortions - Jones, Rachel K. (Contracept X, 2020)
OBJECTIVE: To estimate the number of transgender and gender non-binary (TGNB) individuals who obtained abortions in the United States and the extent to which abortion facilities offer transgender-specific health services. STUDY DESIGN: We collected survey data from all known health care facilities that provided abortions in 2017. For the first time, the questionnaire included items about TGNB abortion patients and services. RESULTS: We estimate that 462 to 530 TGNB individuals obtained abortions in 2017 and that 23% of clinics provide transgender-specific care. CONCLUSION: Several hundred abortions were provided to TGNB individuals in 2017, primarily at facilities that did not provide transgender-specific health services. IMPLICATIONS: Findings from this study support efforts to implement and expand gender-inclusive and affirming care at health care facilities that provide abortion.